New Advances in Monitoring Cardiac Output in Circulatory Mechanical Assistance Devices. A Validation Study in a Porcine Model - Quintana-Villamandos, Begoña; Barranco, Mónica; Fernández, Ignacio; Ruiz, Manuel; del Cañizo, Juan Francisco (Frontiers in Physiology, 2021)
Cardiac output (CO) measurement by continuous pulmonary artery thermodilution (COCTD) has been studied in patients with pulsatile-flow LVADs (left ventricular assist devices), confirming the clinical utility. However, it has not been validated in patients with continuous-flow LVADs. Therefore, the aim of this study was to assess the validity of COCTD in continuous-flow LVADs. Continuous-flow LVADs were implanted in six miniature pigs for partial assistance of the left ventricle. Both methods of measuring CO – measurement by COCTD and intermittent pulmonary artery thermodilution, standard technique (COITD) – were used in four consecutive moments of the study: before starting the LVAD (basal moment), and with the LVAD started in normovolemia, hypervolemia (fluid overloading), and hypovolemia (shock hemorrhage). At the basal moment, COCTD and COITD were closely correlated (r2 = 0.97), with a mean bias of -0.13 ± 0.16 L/min and percentage error of 11%. After 15 minutes of partial support LVAD, COCTD and COITD were closely correlated (r2 = 0.91), with a mean bias of 0.31 ± 0.35 L/min and percentage error of 20%. After inducing hypervolemia, COCTD and COITD were closely correlated (r2 = 0.99), with a mean bias of 0.04 ± 0.07 L/min and percentage error of 5%. After inducing hypovolemia, COCTD and COITD were closely correlated (r2 = 0.74), with a mean bias of 0.08 ± 0.22 L/min and percentage error of 19%. This study shows that continuous pulmonary thermodilution could be an alternative method of monitoring CO in a porcine model with a continuous-flow LVAD..